Prevalence and Risk Factors for Depression among Caregivers of Alzheimer’s Disease Patients in Saudi Arabia - Mohammed Saeed Alqahtani; Ahmad Ayed Alshbriqe; Ahmed A. Awwadh; Turki Ali Alyami; Mohammed Saad Alshomrani; Adel Alhazzani (Neurology Research International)
Objectives. To identify prevalence and risk factors of depression among caregivers of Alzheimer’ disease (AD) patients. Methods. In a cross-sectional study, 110 caregivers of AD patients participated in this study (51 males and 59 females). Patients data were obtained from patients’ records at Aseer Central Hospital. Depression among caregivers was assessed by using the Hamilton Rating Scale for Depression. Results. The age of caregivers ranged from 17 to 85 years (Mean±SD: 41.1±14.0 years). Prevalence of depression among caregivers was 70%. Caregivers were mainly sons/daughters (69.1%) or spouses (11.8%). A total of 33 caregivers (30%) had mild depression while 44 (40%) had moderate depression. Prevalence of depression was significantly higher among caregivers of AD patients who were exposed to repeated falling down (p=0.003), but did not differ significantly among caregivers who were exposed to repeated pneumonia or getting lost. Caregivers’ scores of depression positively correlated with duration of caregivers’ daily stay with AD patients (r=0.272, p=0.004), but did not correlate significantly with either caregivers’ age or patients’ age. Moreover, caregivers’ depression did not differ significantly according to their marital status, educational status, employment status, or monthly income. Conclusions. Prevalence of depression among AD caregiver is high. Risk factors for depression include patients’ exposure to repeated falls and prolonged stay with patients. Therefore, psychiatric care should be provided to caregivers, home safety should be maintained to avoid falls, and several persons should interchangeably provide care to AD patients.